An anisotropic strategy for developing polymer electrolytes endowing lithium metal batteries with electrochemo-mechanically stable interface - Jingren Gou; Kaixuan Cui; Suqing Wang; Zheng Zhang; Jiale Huang; Haihui Wang (Nature Communications)
Abstract Developing versatile solid polymer electrolytes is a reasonable approach to achieving reliable lithium metal batteries but is still challenging due to the nonuniform lithium deposition associated with the sluggish Li+ kinetics and insufficient mechanical strength. Herein, the concept of developing anisotropic solid polymer electrolyte is realized via integrating polymer hosts with highly oriented polyacrylonitrile nanofibers modified by Li6.4La3Zr1.4Ta0.6O12 particles. The oriented composite structure is employed to homogenize Li+ flux, serving as a physical barrier to resist lithium dendrites, retarding the side reaction between the electrolyte and lithium, thus endowing a compatible interface for lithium negative electrode. Correspondingly, the Li | |LiFePO4 cells steadily operate over 1000 cycles, delivering durable capacity retention of 91% at 170 mA g-1. Furthermore, numerical modeling and density functional theory are combined to clarify the multiphysics interplay between the designed solid polymer electrolyte and lithium negative electrode. This work provides a perspective for constructing interface-friendly solid polymer electrolytes at an electrochemo-mechanical level.